Transplantation of mesenchymal stem cells and their derivatives effectively promotes liver regeneration to attenuate acetaminophen-induced liver injury - Hu, Chenxia (Stem Cell Res Ther, 2020)
Acetaminophen (APAP)-induced injury is a common clinical phenomenon that not only occurs in a dose-dependent manner but also occurs in some idiosyncratic individuals in a dose-independent manner. APAP overdose generally results in acute liver injury via the initiation of oxidative stress, endoplasmic reticulum (ER) stress, autophagy, liver inflammation, and microcirculatory dysfunction. Liver transplantation is the only effective strategy for treating APAP-induced liver failure, but liver transplantation is inhibited by scarce availability of donor liver grafts, acute graft rejection, lifelong immunosuppression, and unbearable costs. Currently, N-acetylcysteine (NAC) effectively restores liver functions early after APAP intake, but it does not protect against APAP-induced injury at the late stage. An increasing number of animal studies have demonstrated that mesenchymal stem cells (MSCs) significantly attenuate acute liver injury through their migratory capacity, hepatogenic differentiation, immunoregulatory capacity, and paracrine effects in acute liver failure (ALF). In this review, we comprehensively discuss the mechanisms of APAP overdose-induced liver injury and current therapies for treating APAP-induced liver injury. We then comprehensively summarize recent studies about transplantation of MSC and MSC derivatives for treating APAP-induced liver injury. We firmly believe that MSCs and their derivatives will effectively promote liver regeneration and liver injury repair in APAP overdose-treated animals and patients. To this end, MSC-based therapies may serve as an effective strategy for patients who are waiting for liver transplantation during the early and late stages of APAP-induced ALF in the near future.